"THE FUTURE OF CYBER DEFENSE BY EVALUATING AI'S IMPACT ON SECURITY POSTURES IN INDIAN ORGANIZATIONS" (CAHIERS MAGELLANES-NS, 2024)
In the contemporary digital landscape, the sophistication and prevalence of cyber threats necessitate advanced defense mechanisms. This study explores the transformative role of Artificial Intelligence (AI) in cyber security, focusing on Indian companies and their integration of AI technologies for threat detection and response. By analyzing secondary data from leading cybersecurity firms—Tata Consultancy Services, Wipro, HCL Technologies, Tech Mahindra, and Paladion—over a period from 2019 to 2024, the research investigates the effectiveness of AI-driven solutions and the challenges associated with their implementation. Key findings indicate that AI-driven threat detection and response systems significantly enhance organizational security postures, while threat intelligence services notably improve detection and response times. Despite challenges such as high costs and technical complexities, AI proves to be a critical asset in modern cyber defense strategies. This study underscores the necessity for continuous investment in AI technologies to bolster cyber security defenses against evolving threats.